THE EFFECT OF ROAD INFRASTRUCTURE AND ELECTRICITY CONSUMPTION ON INVESTMENT AND ECONOMIC GROWTH IN BALI PROVINCE - Nur Syifa Eka Putri; Ida Bagus Putu Purbadharmaja (ADISAM Publisher, 2025)
This study aims to evaluate the effect of road infrastructure and electricity consumption on investment levels and economic growth in Bali Province. Infrastructure is considered a crucial element in stimulating economic activity and attracting investment. Adequate road networks facilitate the distribution of goods and services, while sufficient electricity supply serves as an essential enabler for industrial and business activities. This research utilizes secondary data collected from 2019 to 2023, sourced from the Central Statistics Agency (BPS) and other relevant institutions. Data analysis was conducted using panel data regression methods to examine both direct and indirect effects between variables. The Chow test, Hausman test, and Lagrange Multiplier test were employed to determine the most appropriate panel model. The results indicate that road infrastructure has a positive effect on investment. Conversely, electricity consumption shows a negative effect on investment. In terms of economic growth, road infrastructure again exhibits a positive contribution, while electricity consumption demonstrates a negative effect. Furthermore, investment has a positive but statistically insignificant effect on economic growth. The finding of a negative effect from electricity consumption contradicts the initial expectations. This may be due to the fact that high electricity consumption does not necessarily reflect increased productivity. The bulk of electricity usage is likely attributed to the household or tourism sectors, whose contributions to long-term investment and productive sectors are relatively limited. Moreover, economic growth is not found to significantly mediate the relationship between road infrastructure and electricity consumption in enhancing regional economic performance.